World Health Day focus on HIV and depression - a comorbidity with specific challenges. - Sherr, L; Cluver, L (International AIDS Society, 2017)
Depression is intricately bound with HIV. Depression may elevate risks of HIV acquisition and be triggered by an HIV diagnosis, in people living with HIV or in people receiving treatment. Depression is a key comorbidity in HIV. Mental health is often underserved especially in adult care, and more so for children and adolescents – despite the elevated infection rates, nonadherence and mortality in these age groups.